Strategi Belajar Calon Peserta Tenaga Kerja Pada Pelatihan Operator Listrik Industri - Uus Ustiyaroh; Mohammad Fatkhurrokhman; Bagus Dwi Cahyono; Adie Bangga (Peneliti.net, 2023)
Employment issues are inseparable from employment opportunities and economic growth. High economic growth requires investment that can encourage progress and conducive economic policies so as to create new jobs and reduce unemployment. Training is expected to reduce unemployment and improve the lives of competent prospective workers for work or entrepreneurship. The purpose of this study was to reveal the learning strategies of prospective workforce participants in the Industrial Electrical Operator training at the Serang Center for Vocational and Productivity Training (BBPVP). In this study using qualitative methods with a case study approach. The results obtained show the learning strategies of prospective workforce participants, namely: 1) adapting to the instructor (paying attention to the instructor and adapting to applicable rules), 2) learning independently (taking initiative, learning through social media and making improvements), and 3) learning by sharing (discussing with other participants or asking the instructor).